2018
DOI: 10.1002/ece3.4539
|View full text |Cite
|
Sign up to set email alerts
|

Extensive diversity of malaria parasites circulating in Central African bats and monkeys

Abstract: The order Haemosporidia gathers many protozoan parasites which are known to infect many host species and groups. Until recently, the studies on haemosporidian parasites primarily focused on the genus Plasmodium among a wide range of hosts. Genera, like the genus Hepatocystis, have received far less attention. In the present study, we present results of a survey of the diversity of Hepatocystis infecting bats and monkeys living in a same area in Gabon (Central Africa). Phylogenetic analyses revealed a large div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
1
17
1
1
Order By: Relevance
“…The prevalences (of 25 and 42%) are similar to previous reports from epauletted fruit bats in other West, Central and East African countries (e.g. Schaer et al ., 2013; Lutz et al ., 2016; Boundenga et al ., 2018) with the exceptions of the studies in South Sudan and Central Gabon (Schaer et al ., 2017; Rosskopf et al ., 2019). The study in South Sudan revealed Hepatocystis infections in over 80% of the investigated epauletted fruit bats and in contrast, the study in Central Gabon reported no haemosporidian infections in the epauletted fruit bats (Schaer et al ., 2017; Rosskopf et al ., 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prevalences (of 25 and 42%) are similar to previous reports from epauletted fruit bats in other West, Central and East African countries (e.g. Schaer et al ., 2013; Lutz et al ., 2016; Boundenga et al ., 2018) with the exceptions of the studies in South Sudan and Central Gabon (Schaer et al ., 2017; Rosskopf et al ., 2019). The study in South Sudan revealed Hepatocystis infections in over 80% of the investigated epauletted fruit bats and in contrast, the study in Central Gabon reported no haemosporidian infections in the epauletted fruit bats (Schaer et al ., 2017; Rosskopf et al ., 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Apart from these three studies, which date back well over 50 years ago, no infections with haemosporidian parasites have been re-discovered in R. aegyptiacus (e.g. Schaer et al ., 2013; Lutz et al ., 2016; Boundenga et al ., 2018; Rosskopf et al ., 2019). Strikingly, here we detected Hepatocystis parasites, and not the previously reported Plasmodium species in this bat host.…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus that Hepatocystis spp. are nested within the Plasmodium genus (2,8,9), however their placement within the genus has not been robustly determined. Indeed, our cytochrome b phylogeny confirms that our assembled genome is that of Hepatocystis spp., but it provides little support for the placement of this genus in relation to Plasmodium spp.…”
Section: Phylogenetic Position Of Hepatocystis Sp Ex Piliocolobus Tmentioning
confidence: 99%
“…Probabilities of infections were high, and multiple infections were common in the study population, as observed in African great apes (Kaiser et al, 2010; Liu et al, 2010; Otto et al, 2018) but in contrast to captive mandrills living in Southern Gabon (Boundenga et al, 2018; Ngoubangoye et al, 2016). We found also slight evidence that the presence of one Plasmodium species facilitated the establishment of the second species.…”
Section: Discussionmentioning
confidence: 73%